1985
DOI: 10.1073/pnas.82.15.5190
|View full text |Cite
|
Sign up to set email alerts
|

Human plasma kallikrein and C1 inhibitor form a complex possessing an epitope that is not detectable on the parent molecules: demonstration using a monoclonal antibody.

Abstract: The inactivation of human plasma kallikrein (EC 3.4.21.8) by the inhibitor of activated complement component 1 (Ci inhibitor) induces the formation of a 1:1 stoichiometric kallikrein-Ci inhibitor complex and a proteolytically modified form of Ci inhibitor. We have produced a monoclonal antibody that recognizes the kallikrein-Cl inhibitor complex as well as modified C1 inhibitor but fails to react with virgin Ci inhibitor or native plasma kallikrein. This observation constitutes an unequivocal demonstration tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…This indicates that the epitopes recognized by the antibodies are not located in the near vicinity of the active site residues Arg346-Met347 of PAI-I. de Agostini et al [28,29] nor Nuijens et al [30] provided information on the functional effects of their monoclonal antibodies.…”
Section: Detection O]common Neoantigenic Epitopes In Various Pal1mentioning
confidence: 99%
“…This indicates that the epitopes recognized by the antibodies are not located in the near vicinity of the active site residues Arg346-Met347 of PAI-I. de Agostini et al [28,29] nor Nuijens et al [30] provided information on the functional effects of their monoclonal antibodies.…”
Section: Detection O]common Neoantigenic Epitopes In Various Pal1mentioning
confidence: 99%
“…Second, about one-third of native Cl-Inh in plasma is cleaved in vitro to iCl-Inh upon activation of the contact system by kaolin (53) and DXS (45). Third, analytic gel (SDS-PAGE) studies concerning the interaction of Cl-Inh with either kallikrein, Factor XIa, or plasmin have demonstrated the formation of stable high-molecular weight complexes and the appearance of iCl-Inh species (22,(27)(28)(29)56).…”
Section: Ci-cl-inh and Kallikrein-cl-inh Complexes In Patients Withmentioning
confidence: 99%
“…Several studies have shown that the formation of high-molecular weight target proteinase-C1-Inh complexes is accompanied by the generation of modified (cleaved), inactive Cl-Inh (iCl-Inh) species with a lower apparent molecular weight than native Cl-Inh (23,24,(27)(28)(29). In addition, a number ofendogenous (e.g., neutrophil elastase) and bacterial nontarget proteinases (i.e., proteinases that are not inhibited by Cl-Inh) generate iCl-Inh species by catalytical cleavage ofthe inhibitor in its reactive center (30,31).…”
Section: Introductionmentioning
confidence: 99%
“…TPCK-treated bovine trypsin was from Worthington (Freehold, N J) and was active site-titrated with para-nitrophenol guanidinobenzoate [12]. Monoclonal antibodies 3C7 and 4C3 were prepared as described previously [9].…”
Section: Methodsmentioning
confidence: 99%
“…Monoclonal antibody 4C3 binds to cleaved and complexed Cl-inhibitor but not to the native protein [9,10] and is, therefore, an indicator of conformational changes involving the reactive centre loop. Thus, it was tested if polyinerisation could induce the formation of the epitope.…”
Section: Immunoreactivity Of Polymerised Cl-inhibitormentioning
confidence: 99%